Downregulation of the p.A165 risk allele reduces hepatocyte lipid content by increasing beta-oxidation - Ester Ciociola; Tanmoy Dutta; Kavitha Sasidharan; Lohitesh Kovooru; Francesca R. Noto; Grazia Pennisi; Salvatore Petta; Angela Mirarchi; Samantha Maurotti; Bernardette Scopacasa; Luca Tirinato; Patrizio Candeloro; et al. (Clinical and Molecular Hepatology)
Background/Aims Metabolic dysfunction-associated steatotic liver disease (MASLD) is a global epidemic. The disease has a strong genetic component, and a common missense variant (rs2642438) in the mitochondrial amidoxime-reducing component 1 (MARC1) gene confers protection against its onset and severity. However, there are contrasting results regarding the mechanisms that promote this protection. Methods We downregulated MARC1 in primary human hepatocytes (PHHs) using short interfering RNA (siRNA). We measured neutral lipid content by Oil-Red O staining and fatty acid oxidation by radiolabeled tracers. We also performed RNA-sequencing and proteomic analysis using LC-MS. Additionally, we analyzed data from 239,075 participants from the UK Biobank. Results Downregulation of MARC1 reduced neutral lipid content in PHHs homozygous for the wild type (p.A165, risk), but not for the mutant (p.T165, protective), allele. We found that this reduction was mediated by increased fatty acid utilization via β-oxidation. Consistent with these results, we found that the levels of 3-hydroxybutyrate, a by-product of β-oxidation, were higher in carriers of the rs2642438 minor allele among samples from the UK biobank, indicating higher β-oxidation in these individuals. Moreover, downregulation of the MARC1 p.A165 variant resulted in a more favorable phenotype by reducing ferroptosis and reactive oxygen species levels. Conclusions MARC1 downregulation in carriers of the risk allele results in lower hepatocyte neutral lipids content due to higher β-oxidation, while upregulating beneficial pathways involved in cell survival.